2015
DOI: 10.1016/j.freeradbiomed.2015.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent deleterious and salutary actions of the Nrf2 inducer dh404 in chronic kidney disease

Abstract: Oxidative stress and inflammation play a central role in progression and complications of CKD and are, in part, due to impairment of the Nrf2 system which regulates expression of antioxidant and detoxifying molecules. Natural Nrf2 inducing phytochemicals have been shown to ameliorate kidney disease in experimental animals. However due to adverse outcomes clinical trial of synthetic Nrf2 activator, bardoxolone methyl (BARD), in CKD patients was terminated. BARD activates Nrf2 via 2 covalent modification of reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 58 publications
2
24
0
Order By: Relevance
“…23 On the other hand, in Zucker diabetic fatty rats, a model of type 2 diabetes mellitus with progressive renal disease treatment with RTA 405, a bardoxolone analogue, caused worsening of proteinuria, glomerulosclerosis, and tubular damage. 24,25 Clinical studies have also shown discordant results. In the phase II Trial to Determine the Effects of Bardoxolone Methyl on eGFR in Patients With Type 2 Diabetes and Chronic Kidney Disease (BEAM study), patients with chronic kidney disease treated with bardoxolone had significantly improved renal function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 On the other hand, in Zucker diabetic fatty rats, a model of type 2 diabetes mellitus with progressive renal disease treatment with RTA 405, a bardoxolone analogue, caused worsening of proteinuria, glomerulosclerosis, and tubular damage. 24,25 Clinical studies have also shown discordant results. In the phase II Trial to Determine the Effects of Bardoxolone Methyl on eGFR in Patients With Type 2 Diabetes and Chronic Kidney Disease (BEAM study), patients with chronic kidney disease treated with bardoxolone had significantly improved renal function.…”
Section: Discussionmentioning
confidence: 99%
“…27 Reasons for these dimorphic findings may relate, in part, to the doses of drugs used as suggested in studies of chronic kidney disease, where the bardoxolone analogue, dh404, at low doses restored Nrf2 activity and reduced glomerulosclerosis, whereas at high doses intensified proteinuria and aggravated renal dysfunction and kidney fibrosis. 25,28 A few studies have shown that Nrf2 is dysregulated in models of hypertension and that Nrf2 activators prevent blood pressure elevation. In mice with renal dopamine 2 receptor deficiency, elevated blood pressure and reduced renal Nrf2 expression were normalized by bardoxolone.…”
Section: Discussionmentioning
confidence: 99%
“…38 However, some studies demonstrated deleterious effects of Nrf2. The Nrf2 activator bardoxolone worsened proteinuria, glomerulosclerosis, and tubular damage in a model of type 2 DM, 39,40 as well as renal function in a phase II clinical trial. 41 In addition, a trial was prematurely terminated because of higher incidence of heart failure and mortality in bardoxolone-treated patients.…”
Section: Figure 2 High Glucose (Hg)-induced Reactive Oxygen Species mentioning
confidence: 97%
“…42 Additional studies demonstrated that although low doses of Nrf2 activators are protective, high doses lead to deleterious outcomes. 40,43 In basal conditions, Keap1, which regulates Nrf2 ubiquitination via Cul3-Keap1, keeps Nrf2 in the cytosol. In oxidative stress conditions, it is expected that Cul3-Keap1-E3 ligase is inhibited by oxidation, releasing Nrf2, which translocates to the nucleus, binds to antioxidant response element, and initiates transcription of antioxidant enzymes.…”
Section: Figure 2 High Glucose (Hg)-induced Reactive Oxygen Species mentioning
confidence: 99%
See 1 more Smart Citation